C.5 IB - Bagchi, Amiya Kumar (ed.) (Calcutta, 1988)
This book cover following topics The story if land reforms in Indian Planning, Foodgrain stocks and prices, The unorganized sector and the planner and Indian planning and regional disparity in growth.
Keywords: "Datta, Bhabatosh"